Cybernated storytelling: Revitalising storytelling activities for secondary school students - Roziana, Mohamed Rosli; Faizah, Idrus (IATEFL Poland Computer Special Interest Group, 2017)
Storytelling is one of the most common activities used in teaching English proficiency to language students. It is widely accepted as a teaching technique by many educators because it engages students in learning. This study seeks to examine students’ readiness in using technology-aided applications in telling their stories. It also investigates how cybernated storytelling could encourage them to communicate more in groups. This qualitative study involved 35 secondary school students, selected based on purposive sampling technique, from a multi-ethnic secondary school in Malaysia. After having initial exposure to cybernated storytelling video production, the students were divided into small groups and required to engage in developing a cybernated storytelling video for a period of 90 days using the English language. While engaging in the activity, students were expected to communicate orally in face-to-face meetings and in writing using WhatsApp (WA) and Facebook (FB) platforms. Their WA and FB entries were compiled and analysed thematically besides interview responses which were collected during the group interview. The findings point to how technology aided language learning could be a strong support in enhancing students’ English communication skills.